Genome-Wide Identification of MESP1 Targets Demonstrates Primary Regulation Over Mesendoderm Gene Activity. (18th August 2015) - Soibam, Benjamin; Benham, Ashley; Kim, Jong; Weng, Kuo-Chan; Yang, Litao; Xu, Xueping; Robertson, Matthew; Azares, Alon; Cooney, Austin J.; Schwartz, Robert J.; Liu, Yu
Abstract: MESP1 is considered the first sign of the nascent cardiac mesoderm and plays a critical role in the appearance of cardiac progenitors, while exhibiting a transient expression in the developing embryo. We profiled the transcriptome of a pure population of differentiating MESP1-marked cells and found that they chiefly contribute to the mesendoderm lineage. High-throughput sequencing of endogenous MESP1-bound DNA revealed that MESP1 preferentially binds to two variants of E-box sequences and activates critical mesendoderm modulators, including Eomes, Gata4, Wnt5a, Wnt5b, Mixl1, T, Gsc, and Wnt3 . These mesendoderm markers were enriched in the MESP1 marked population before the appearance of cardiac progenitors and myocytes. Further, MESP1-binding is globally associated with H3 K27 acetylation, supporting a novel pivotal role of it in regulating target gene epigenetics. Therefore, MESP1, the pioneer cardiac factor, primarily directs the appearance of mesendoderm, the intermediary of the earliest progenitors of mesoderm and endoderm organogenesis. Stem Cells 2015;33:3254–3265